2018
DOI: 10.1159/000488021
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Findings of Malignant and Benign Head and Neck Masses in Somalia

Abstract: Objective: There are no up-to-date records on head and neck masses (HNMs) in Somalia. This cytological study is the first to demonstrate the benefits and findings of fine-needle aspiration cytology in evaluating HNMs in the adult population of Somalia. Study Design: A total of 116 aspiration samples were taken from different levels of the neck region, except for the thyroid. Cases were classified as salivary gland, lymph node, or soft tissue/cystic lesions. They were classified according to age, gender, and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The correlation between pathological responsiveness and each clinicopathological factor was analysed comparatively using the chi-square test. The Kaplan–Meier survival curve and log-rank method were used to analyse the relationship between tumour pathological responsiveness and recurrence-free survival and overall survival after adjuvant therapy [ 18 ]. The ROC curve actually represents a stochastic classifier.…”
Section: Related Workmentioning
confidence: 99%
“…The correlation between pathological responsiveness and each clinicopathological factor was analysed comparatively using the chi-square test. The Kaplan–Meier survival curve and log-rank method were used to analyse the relationship between tumour pathological responsiveness and recurrence-free survival and overall survival after adjuvant therapy [ 18 ]. The ROC curve actually represents a stochastic classifier.…”
Section: Related Workmentioning
confidence: 99%
“…In many reports, TB was the most common cause of cervical lymphadenopathy in tropical regions. 13 Sarda et al 17 found that 86% of cervical lymphadenopathies were of TB origin. This high rate indicates that lymph node biopsy was performed with good clinical screening and possibly appropriate patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, TB dominance in Somalia stands out. In many reports, TB was the most common cause of cervical lymphadenopathy in tropical regions 13 . Sarda et al 17 found that 86% of cervical lymphadenopathies were of TB origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations